2010
DOI: 10.1016/j.wear.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Tribological study of Fe–Cu–Cr–graphite alloy and cast iron railway brake shoes by pin-on-disc technique

Abstract: ElsevierFerrer Giménez, C.; Pascual Guillamón, M.; Busquets Mataix, DJ.; E. Rayón (2010) AbstractA new class of materials is being installed in railway brake blocks to substitute classic cast iron in order to reduce the rolling noise produced by the roughness of the treadwheel surface. The tribological properties of cast iron and Fe-Cu-Cr-graphite sintered alloy brake shoes were analyzed. Kinetic friction coefficient (μ) and wear were monitored by means of a pin-on-disc technique. The sintered alloy brake sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Reasonably accurate fits to the experimental data suggests that the functional form considered for apparent friction coefficient is adequate. It may be noted that these observations are in line with those made by Ferrer et al [4] using pin on disc experiments with discs extracted from locomotive wheel and pins extracted from the brake blocks. Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Reasonably accurate fits to the experimental data suggests that the functional form considered for apparent friction coefficient is adequate. It may be noted that these observations are in line with those made by Ferrer et al [4] using pin on disc experiments with discs extracted from locomotive wheel and pins extracted from the brake blocks. Fig.…”
Section: Resultssupporting
confidence: 91%
“…Experiments revealed that irrespective of graphite morphology used in brake shoes, friction coefficient decreased with increasing brake pressure and sliding velocity until it reached a critical value. Ferrer et al [4] conducted pin-on-disc experiments for gray cast iron and sintered brake blocks for different sliding velocities and brake pressures. Experiments showed that for a given brake pressure and sliding velocity, sintered brake shoes exhibit higher friction coefficient and wear than cast iron brake shoes.…”
Section: Introductionmentioning
confidence: 99%
“…Tribological tests were carried out under a pin-on-disc configuration on a CETR UMT multi-specimen test system [14][15][16][17] as shown in Fig. 3a.…”
Section: Tribological Testmentioning
confidence: 99%
“…Over the last two decades, a polymer composite brake block has been developed to replace the cast iron brake block. The application of composite brake blocks has some advantages in that they reduce noise [2], have a low specific wear [3], and are lightweight. To avoid excessive wear on the wheel tread surface, the wheel material should be harder than the brake block material.…”
Section: Introductionmentioning
confidence: 99%